Femoral vein homograft as Sano shunt results in improved pulmonary artery growth after Norwood operation. (29th August 2017) - Briceno-Medina, Mario; Kumar, T. K. Susheel; Sathanandam, Shyam; Boston, Umar; Perez, Michael; Allen, Jerry; Zurakowski, David; Ilbawi, Michel; Knott-Craig, Christopher J.
Abstract: Objective: To evaluate differences in interstage growth of pulmonary arteries between use of polytetrafluoroethylene and femoral vein homograft as Sano shunt during stage-I Norwood palliation. Methods: A retrospective review of all patients who survived to the second stage following Norwood–Sano operation at two institutions was performed. Either polytetrafluoroethylene or the valved segment of femoral vein homograft was used for construction of the Sano shunt. The size of pulmonary arteries was compared at pre-Glenn catheterisation. Results: A total of 48 neonates with the diagnosis of hypoplastic left heart syndrome or its variants comprised the study population. Femoral vein homograft of 5–6 mm diameter was used in 14 and polytetrafluoroethylene graft of 5 mm was used in 34 patients. The two groups were comparable in terms of preoperative demographics and age at time of pre-Glenn catheterisation (3.9±0.7 versus 3.4±0.8 months, p=0.06). Patients who received femoral vein homograft demonstrated a significantly higher pre-Glenn Nakata index [264 (130–460) versus 165 (108–234) mm 2 /m 2, p=0.004]. The individual branch pulmonary arteries were significantly larger in the femoral vein group (right, 7.8±3.6 versus 5.0±1.2, p=0.014; left, 7.2±2.1 versus 5.6±1.9, p=0.02). There were no differences in cardiac index, Qp:Qs, ventricular end-diastolic pressure or systemic oxygen saturations. Conclusions: Utilisation of a valved segment of femoral vein homograft as right ventricle to pulmonary artery conduit during Norwood–Sano operation confers better interstage growth of the pulmonary arteries. Further studies are needed to evaluate the impact of femoral vein homograft on single ventricle function.